Assessment of Regional Wall Motion Abnormality in Patients with Acute Anteroseptal ST Segment Elevation Myocardial Infarction - Khan, Tunaggina Afrin; Ahmed, Saiful; Haque, Mostashirul; Amin, Md Rasul; Hasan, ATM Iqbal; Arzu, Jahanara; Rahman, Aparna; Zahid, Md Abu (University Heart Journal, 2019)
Post myocardial infarction (MI) short and long term clinical outcome is largely determined by the size of the infarcted area. It is generally assumed that as the lead involvement in the 12 lead electrocardiography (ECG) is less in anteroseptal ST segment elevation myocardial infarction (AS-STEMI), where ST segment elevation (STE) is limited to leads V1 to V3, myocardial damage is likely to be less. This study was intended to assess regional wall motion abnormality (RWMA) in acute anteroseptal STEMI patients. 90 patients with AS-STEMI admitted in between October 2012 and September 2013, were included. For each patient, a transthoracic echocardiogram (TTE) was performed within 24-48 hours of MI and was interpreted by an independent investigator blinded to the patient’s ECG data.The mean (± SD) age of the patients was 51.57 (± 12.02) years with mean (± SD) age of the patients was 52.58 (± 12.02) years with a range of 23 - 80 years. There were 91.1% male and 8.9% female. The mean (± SD) EF% was 38.80 %( ± 5.78). All the segments of left ventricle, except basal and mid inferolateral segments, were affected in anteroseptal STEMI. So, the term AS-STEMI may be a misnomer, as it implies that only the anteroseptal segments of the left ventricle are involved. This study shows that regional dysfunction in patients with AS-STEMI extends beyond the anteroseptal region and may be it is as much extensive as extensive anterior myocardial infarction. So, any patients with anterior wall involvement should be treated with utmost importance. University Heart Journal Vol. 15, No. 1, Jan 2019; 28-33